Improving Students' Speaking Skills through English Movie - Umitnana, Maria Radegunda; Pale, Erlinda Sonya; Bouk, Edmundus (International Journal of English Education and Linguistics (IJoEEL), 2024)
The Speaking is a complex language skill that involves not only articulating words and sentences but also expanding and expressing ideas meaningfully. This study investigates how using Disney's "Moana" as a teaching tool improves speaking skills in second-grade students at SMPN 1 Biboki Selatan, focusing on pronunciation, vocabulary, grammar, and fluency. Employing Classroom Action Research (CAR) and mixed methods, the study involved 16 students from class VIIIA. Initial speaking test scores averaged 59.06%, with only 37.5% meeting the KKM (75%). After Cycle 1, scores rose to 73.12% with 56.25% meeting the KKM, and in Cycle 2, scores further increased to 86.25%, with all students meeting the KKM. Observations indicated that student activity improved from 72.72% in Cycle 1 to 83.63% in Cycle 2, demonstrating increased engagement. These findings show significant improvements in students' speaking skills and participation, validating the effectiveness of using English movies in language learning. The consistent score increases and enhanced student engagement highlight the success of the CAR approach, making further cycles unnecessary as all students achieved high mastery levels by the end of Cycle 2.